Analysis of Economic Development Planning on Human Development - Rifqah Harahap; M. Asbullah; Indra Ismayudi Tanjung; Liasulistia Ningsih; Mutiara Shifa (Indonesian Journal Economic Review (IJER), 2026)
The purpose of this study is to examine the conceptual analysis of economic development planning to human development. The conceptual analysis in this study aims to provide an in-depth explanation of economic development planning to human development, using secondary data in the form of related books and journal articles. The research results from a conceptual analysis perspective show that economic development planning to human development shifts the focus of the development paradigm from capital-centric, oriented toward capital accumulation and gross domestic product growth, to human-centric, oriented toward expanding human capabilities and well-being. Economic development planning is an instrument of socio-economic engineering, while human development is its moral compass and ultimate goal. A well-thought-out development plan rejects the assumption that economic growth automatically trickles down. Instead, it consciously invests economic capital into human capital, creating a virtuous cycle in which qualified people will drive much stronger, innovative, and sustainable economic growth.